2008
DOI: 10.1210/jc.2008-0255
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary and Testicular Function in Sons of Women with Polycystic Ovary Syndrome from Infancy to Adulthood

Abstract: AMH concentrations are increased in prepubertal sons of women with PCOS, suggesting that these boys may show an increased Sertoli cell number or function during infancy and childhood. However, this does not seem to have a major deleterious effect on sperm production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
5
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 38 publications
1
38
5
1
Order By: Relevance
“…It seems that prenatal excess androgen may lead to reduction of testosterone level after puberty. However in human studies, the serum concentration of testosterone in boys born to mothers with polycystic ovary syndrome was not significantly different from the offspring of healthy women [25], results not in agreement with ours; this difference could be explained by the fact that these boys were exposed to androgen excess throughout their fetal life, whereas in our study fetuses were exposed to exogenous androgen only during a specific period of their fetal life.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It seems that prenatal excess androgen may lead to reduction of testosterone level after puberty. However in human studies, the serum concentration of testosterone in boys born to mothers with polycystic ovary syndrome was not significantly different from the offspring of healthy women [25], results not in agreement with ours; this difference could be explained by the fact that these boys were exposed to androgen excess throughout their fetal life, whereas in our study fetuses were exposed to exogenous androgen only during a specific period of their fetal life.…”
Section: Discussioncontrasting
confidence: 99%
“…One study of sheep supported the negative effect of prenatal exposure to androgen excess on the quality and quantity of sperm after puberty [1]. Significant reduction of sperm count and fertility was observed in men with congenital adrenal hyperplasia, exposed to high amounts of androgens during their fetal life [29,30]; however it was not reported in boys born from mothers with polycystic ovary syndrome (PCOS) [25]. Although men exposed to high androgens during the fetal life, have different presentations after puberty, possibly explained by different types of androgens resulting from the mentioned early [25,29,30], another reason is because the placenta converts the androgen to estrogen via aromatase enzyme [1] probably, in sons of women with polycystic ovary syndrome the amount of androgen metabolized by placenta, while the male fetus with congenital adrenal hyperplasia, fetus is exposed to androgen, directly, during fetal life.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, such studies would provide more detailed information on the neuroendocrine regulation of gonadotropin secretion (44) and a direct assessment of spermatogenesis in male PCOS relatives, respectively. It is noteworthy that no differences in sperm parameters were found by Chilean investigators (8) in adult sons of women with PCOS.…”
Section: Discussionmentioning
confidence: 75%
“…Since 2006 we have published four studies in infants using the leuprolide test and we have not observed any side effects (27)(28)(29)31).…”
Section: Figurementioning
confidence: 79%